Method for optimizing quality of perovskite layer through atmosphere annealing

By using nitrogen atmosphere annealing method in the preparation of perovskite solar cell thin films, the problems of grain boundary defects and surface roughness are solved, the crystal quality and environmental stability of the film are improved, and the service life of the battery is extended.

CN119300688APending Publication Date: 2025-01-10FLAT GLASS GROUP CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411308475.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During the preparation process, perovskite solar cell films face problems such as grain boundary defects, surface roughness and poor environmental stability, which affect their efficiency and long-term stability.

Method used

The nitrogen atmosphere annealing method is used to optimize the quality of the perovskite layer. By selecting the appropriate annealing temperature and time, high-purity nitrogen is used to replace air in the vacuum cavity to reduce grain boundary defects and surface roughness, and improve the crystallization quality of the perovskite film. and surface flatness.

Benefits of technology

The grain size and interface recombination of the perovskite film are improved, the open circuit voltage and filling factor of the battery are enhanced, the overall efficiency is increased by 5 to 8%, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a method for optimizing the quality of a perovskite layer through atmosphere annealing, and belongs to the technical field of perovskite layer quality optimization, and the method comprises the steps: preparing precursor materials: taking methylamine hydrochloride, cesium iodide, formamidine iodide and lead iodide as perovskite precursor materials; the preparation method comprises the following steps: preparing a solvent: mixing N-methyl pyrrolidone with dimethylformamide; solution preparation: mixing the precursor material with a solvent to prepare a precursor solution; stirring and filtering the solution; preparing a substrate: sputtering NiO serving as a hole transport layer material on the glass substrate; blade coating of a perovskite precursor solution: uniformly blade coating the precursor solution on the glass substrate coated with the NiO film; preliminary drying; vacuum annealing preparation: placing the glass substrate coated with the perovskite precursor film in a vacuum cavity; nitrogen atmosphere filling: filling high-purity nitrogen; in the nitrogen atmosphere, the temperature in the cavity is increased to a certain temperature range, annealing is conducted at the temperature, and the optimized annealing temperature and time are selected; and cooling and packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite layer quality optimization, and in particular to a method for optimizing the quality of a perovskite layer through atmosphere annealing. Background Art

[0002] In recent years, perovskite solar cells have become a research hotspot in the photovoltaic field due to their high photoelectric conversion efficiency, low-cost preparation methods, and tunable band gap. However, perovskite films often face problems such as grain boundary defects, surface roughness, and poor environmental stability during the preparation process, which seriously restrict the efficiency and long-term stability of perovskite solar cells. In order to improve the quality of perovskite films and optimize their crystal structure and surface morphology, researchers continue to explore various preparation processes and improvement methods. Summary of the invention

[0003] In order to overcome the above-mentioned defects of the prior art, the present invention provides a method for optimizing the quality of the perovskite layer by annealing in a nitrogen atmosphere to solve the technical problems raised in the background technology.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides a method for optimizing the quality of the perovskite layer by atmosphere annealing, the method comprising:

[0005] Prepare precursor materials:

[0006] Using methylamine hydrochloride, cesium iodide, formamidine iodide, and lead iodide as perovskite precursor materials;

[0007] Prepare solvent:

[0008] Mixing N-methylpyrrolidone and dimethylformamide in a volume ratio of 4:1 as a solvent for dissolving the precursor material;

[0009] Solution preparation:

[0010] Methylamine hydrochloride, cesium iodide, formamidine iodide, and lead iodide are mixed in proportion and dissolved in a mixed solvent of N-methylpyrrolidone and dimethylformamide to prepare a perovskite precursor solution with a concentration of 1M to 1.5M;

[0011] Solution stirring and filtration:

[0012] At room temperature, the prepared perovskite precursor solution is magnetically stirred for 2 to 4 hours to ensure that each component is fully dissolved and forms a uniform mixture, and then allowed to stand for more than 1 hour to allow the impurities in the solution to settle, and finally the solution is filtered through a filter membrane to remove undissolved particles and impurities to ensure the purity of the perovskite precursor solution;

[0013] Substrate preparation:

[0014] NiO was selected as the hole transport layer material. NiO was first deposited on a clean glass substrate by magnetron sputtering, and then the glass substrate was annealed in air to improve the crystal quality and conductivity of the NiO film.

[0015] Doctor coating of perovskite precursor solution:

[0016] The filtered perovskite precursor solution is evenly scraped on the glass substrate coated with NiO film. In order to ensure the uniformity of the film, the scraping speed and thickness are controlled;

[0017] Initial drying:

[0018] After the perovskite precursor solution is applied by scraping, the substrate is placed in the air for a period of time to volatilize part of the solvent and form a preliminary perovskite precursor film;

[0019] Vacuum annealing preparation:

[0020] The glass substrate coated with the perovskite precursor film is placed in a vacuum chamber, and the chamber is evacuated using a vacuum pump to remove air impurities and moisture in the chamber;

[0021] Nitrogen atmosphere filling:

[0022] When the cavity reaches the target vacuum degree, high-purity nitrogen is gradually filled through the control system to restore the air pressure in the cavity to normal atmospheric pressure, so as to ensure that the cavity is an oxygen-free environment, which is beneficial to the crystallization quality of perovskite.

[0023] annealing:

[0024] In a nitrogen atmosphere, the temperature in the cavity is raised to a certain temperature range and maintained at this temperature for annealing. By selecting the optimized annealing temperature and time, the uniform growth of perovskite crystals is promoted and the grain boundary defects and surface roughness are reduced.

[0025] Cooling and packaging:

[0026] After annealing, the cavity is slowly cooled to room temperature to avoid film cracking or structural damage caused by rapid cooling, and packaging is completed after preparation.

[0027] Furthermore, in the vacuum annealing preparation step, a vacuum pump is used to evacuate the vacuum cavity to a vacuum degree of about 4×10-1 Pa to remove air impurities and moisture in the cavity.

[0028] Furthermore, in the annealing step, the temperature in the cavity is raised to 150° C. to 200° C. in a nitrogen atmosphere, and the temperature is maintained for annealing for 10 to 30 minutes.

[0029] Furthermore, in the step of scraping the perovskite precursor solution, the thickness of the perovskite film formed after scraping the perovskite precursor solution is 300 to 600 nanometers.

[0030] Furthermore, in the substrate preparation step, the glass substrate is annealed in air at a temperature of 280° C. to 330° C. for 30 to 60 minutes to improve the crystal quality and conductivity of the NiO film.

[0031] Furthermore, during the stirring and filtering of the solution, the settled perovskite precursor solution is filtered through a filter membrane with a pore size of 0.35 to 0.55 μm.

[0032] Furthermore, in the solution preparation step, the ratio of MACl to CsI, FAI, and PbI2 is 0.95:0.02-0.08:3, wherein the ratio of MACl to CsI is 0.93-0.97:0.03-0.07.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The nitrogen atmosphere annealing method of the present application can improve the crystallization quality and surface flatness of the perovskite film and reduce grain boundary defects. Specific experiments show that nitrogen annealing can increase the grain size of the perovskite layer, reduce interface recombination, increase the open circuit voltage and fill factor of the battery, and improve the overall efficiency by 5 to 8%. In addition, the optimization of the annealing atmosphere can also improve the environmental stability of the perovskite layer and increase the service life of the battery. DETAILED DESCRIPTION

[0035] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the invention, not all of the embodiments. The embodiments of the present invention are described below in combination.

[0036] Thermal annealing is usually used to improve the crystallization quality and optoelectronic properties of perovskite films. However, traditional air or inert atmosphere annealing methods often fail to take into account the uniformity, crystallinity and stability of perovskite films. Although annealing in air can effectively promote the growth of perovskite crystals, it is easy to cause oxidative decomposition of perovskite materials, thereby reducing the stability of the film and the service life of the battery. Although annealing in inert atmospheres such as nitrogen and argon can avoid oxidation problems to a certain extent, it still has certain limitations in reducing grain boundary defects and improving film surface quality.

[0037] At present, research has found that annealing treatments in different atmospheres have a significant effect on the crystal growth, surface flatness and electrical properties of perovskite films. For example, annealing treatments in a nitrogen atmosphere can effectively reduce grain boundary defects in the film and improve crystal uniformity, thereby improving the photoelectric conversion efficiency of perovskite solar cells. Further research also shows that optimizing the annealing atmosphere and temperature conditions can not only improve the microstructure of the film, but also enhance its environmental stability and extend the service life of the battery.

[0038] The present application optimizes the quality of the perovskite layer by an atmosphere annealing method. Selecting an appropriate annealing atmosphere can optimize the growth conditions of the perovskite crystal and reduce grain boundary defects and surface roughness;

[0039] The method for optimizing the quality of the perovskite layer by atmosphere annealing comprises the following steps:

[0040] Prepare precursor materials:

[0041] Using methylamine hydrochloride, cesium iodide, formamidine iodide, and lead iodide as perovskite precursor materials;

[0042] Prepare solvent:

[0043] Mixing N-methylpyrrolidone and dimethylformamide in a volume ratio of 4:1 as a solvent for dissolving the precursor material;

[0044] Solution preparation:

[0045] Methylamine hydrochloride, cesium iodide, formamidine iodine, and lead iodide are mixed in proportion, wherein the ratio of methylamine hydrochloride to cesium iodide, formamidine iodine, and lead iodide is 0.95:0.02-0.08:3, and the ratio of methylamine hydrochloride to cesium iodide is 0.93-0.97:0.03-0.07. In other embodiments of this embodiment, the ratio of methylamine hydrochloride to cesium iodide, formamidine iodine, and lead iodide is 0.95:0.05:3, and the ratio of methylamine hydrochloride to cesium iodide is 0.95:0.05, and the mixture is dissolved in a mixed solvent of N-methylpyrrolidone and dimethylformamide to prepare a perovskite precursor solution with a concentration of 1M to 1.5M;

[0046] Solution stirring and filtration:

[0047] At room temperature, the prepared perovskite precursor solution is magnetically stirred for 2 to 4 hours to ensure that each component is fully dissolved and forms a uniform mixture, and then allowed to stand for more than 1 hour to allow impurities in the solution to settle, and the solution is filtered through a filter membrane. The settled perovskite precursor solution is filtered through a filter membrane with a pore size of 0.35 to 0.55 μm to remove undissolved particles and impurities to ensure the purity of the perovskite precursor solution;

[0048] Substrate preparation:

[0049] NiO is selected as the hole transport layer material. NiO is firstly deposited on a clean glass substrate by magnetron sputtering, and then the glass substrate is annealed in air at a temperature of 280° C. to 330° C. for 30 to 60 minutes to improve the crystal quality and conductivity of the NiO film. In other implementations of this embodiment, the glass substrate is annealed in air at a temperature of 300° C. for 45 minutes;

[0050] Doctor coating of perovskite precursor solution:

[0051] The filtered perovskite precursor solution is evenly scraped on the glass substrate coated with the NiO film. In order to ensure the uniformity of the film, the scraping speed and thickness are controlled. The thickness of the perovskite film formed after scraping the perovskite precursor solution is 300 to 600 nanometers.

[0052] Initial drying:

[0053] After the perovskite precursor solution is applied by scraping, the substrate is placed in the air for a period of time to volatilize part of the solvent and form a preliminary perovskite precursor film;

[0054] Vacuum annealing preparation:

[0055] The glass substrate coated with the perovskite precursor film is placed in a vacuum chamber, and the chamber is evacuated using a vacuum pump. The vacuum degree of the vacuum chamber is evacuated to about 4×10-1Pa using a vacuum pump to remove air impurities and moisture in the chamber;

[0056] Nitrogen atmosphere filling:

[0057] When the cavity reaches the target vacuum degree, high-purity nitrogen is gradually filled through the control system to restore the air pressure in the cavity to normal atmospheric pressure, so as to ensure that the cavity is an oxygen-free environment, which is beneficial to the crystallization quality of perovskite.

[0058] annealing:

[0059] In a nitrogen atmosphere, or in other gases such as argon, the temperature in the cavity is raised to 150° C. to 200° C., and the temperature is maintained for annealing for 10 to 30 minutes. By selecting the optimized annealing temperature and time, the uniform growth of the perovskite crystal is promoted, and the grain boundary defects and surface roughness are reduced. In other implementations of this embodiment, the annealing is to raise the temperature in the cavity to 180° C. in a nitrogen atmosphere, and maintain the temperature for annealing for 20 minutes;

[0060] Cooling and packaging:

[0061] After annealing, the cavity is slowly cooled to room temperature to avoid film cracking or structural damage caused by rapid cooling, and packaging is completed after preparation.

[0062] The nitrogen atmosphere annealing method of the present application can improve the crystallization quality and surface flatness of the perovskite film and reduce grain boundary defects. Specific experiments show that nitrogen annealing can increase the grain size of the perovskite layer, reduce interface recombination, increase the open circuit voltage and fill factor of the battery, and improve the overall efficiency by 5 to 8%. In addition, the optimization of the annealing atmosphere can also improve the environmental stability of the perovskite layer and increase the service life of the battery.

[0063] The technical solution of the present invention is described above in conjunction with specific implementation methods, but it should be noted that the above descriptions are only for explaining the solution of the present invention and cannot be interpreted in any way as a specific limitation on the scope of protection of the invention. Based on the explanation here, those skilled in the art can think of other specific implementation methods or equivalent replacements of the present invention without creative work, and they will all fall within the scope of protection of the present invention.

Claims

1. A method for optimizing the quality of a perovskite layer by atmosphere annealing, characterized in that: The method comprises: Prepare precursor materials: Using methylamine hydrochloride, cesium iodide, formamidine iodide, and lead iodide as perovskite precursor materials; Prepare solvent: Mixing N-methylpyrrolidone and dimethylformamide in a volume ratio of 4:1 as a solvent for dissolving the precursor material; Solution preparation: Methylamine hydrochloride, cesium iodide, formamidine iodide, and lead iodide are mixed in proportion and dissolved in a mixed solvent of N-methylpyrrolidone and dimethylformamide to prepare a perovskite precursor solution with a concentration of 1M to 1.5M; Solution stirring and filtration: At room temperature, the prepared perovskite precursor solution is magnetically stirred for 2 to 4 hours to ensure that each component is fully dissolved and forms a uniform mixture, and then allowed to stand for more than 1 hour to allow the impurities in the solution to settle, and finally the solution is filtered through a filter membrane to remove undissolved particles and impurities to ensure the purity of the perovskite precursor solution; Substrate preparation: NiO was selected as the hole transport layer material. NiO was first deposited on a clean glass substrate by magnetron sputtering, and then the glass substrate was annealed in air to improve the crystal quality and conductivity of the NiO film. Doctor coating of perovskite precursor solution: The filtered perovskite precursor solution is evenly scraped on the glass substrate coated with NiO film. In order to ensure the uniformity of the film, the scraping speed and thickness are controlled; Initial drying: After the perovskite precursor solution is applied by scraping, the substrate is placed in the air for a period of time to volatilize part of the solvent and form a preliminary perovskite precursor film; Vacuum annealing preparation: The glass substrate coated with the perovskite precursor film is placed in a vacuum chamber, and the chamber is evacuated using a vacuum pump to remove air impurities and moisture in the chamber; Nitrogen atmosphere filling: When the cavity reaches the target vacuum degree, high-purity nitrogen is gradually filled through the control system to restore the air pressure in the cavity to normal atmospheric pressure, so as to ensure that the cavity is an oxygen-free environment, which is beneficial to the crystallization quality of perovskite. annealing: In a nitrogen atmosphere, the temperature in the cavity is raised to a certain temperature range and maintained at this temperature for annealing. By selecting the optimized annealing temperature and time, the uniform growth of perovskite crystals is promoted and the grain boundary defects and surface roughness are reduced. Cooling and packaging: After annealing, the cavity is slowly cooled to room temperature to avoid film cracking or structural damage caused by rapid cooling, and packaging is completed after preparation.

2. The method for optimizing the quality of the perovskite layer by atmosphere annealing according to claim 1, characterized in that: In the vacuum annealing preparation step, a vacuum pump is used to evacuate the vacuum degree of the vacuum chamber to about 4×10-1 Pa to remove air impurities and moisture in the chamber.

3. The method for optimizing the quality of the perovskite layer by atmosphere annealing according to claim 1, characterized in that: In the annealing step, the temperature in the chamber is raised to 150° C. to 200° C. in a nitrogen atmosphere, and the temperature is maintained for annealing for 10 to 30 minutes.

4. The method for optimizing the quality of the perovskite layer by atmosphere annealing according to claim 1, characterized in that: In the step of scraping the perovskite precursor solution, the thickness of the perovskite film formed after scraping the perovskite precursor solution is 300 to 600 nanometers.

5. The method for optimizing the quality of the perovskite layer by atmosphere annealing according to claim 1, characterized in that: In the substrate preparation step, the glass substrate is annealed in air at a temperature of 280° C. to 330° C. for 30 to 60 minutes to improve the crystal quality and conductivity of the NiO film.

6. The method for optimizing the quality of the perovskite layer by atmosphere annealing according to claim 1, characterized in that: During the stirring and filtering of the solution, the settled perovskite precursor solution is filtered through a filter membrane with a pore size of 0.35 to 0.55 μm.

7. The method for optimizing the quality of the perovskite layer by atmosphere annealing according to claim 1, characterized in that: In the solution preparation step, the ratio of MACl to CsI, FAI, and PbI2 is 0.95:0.02-0.08:3, wherein the ratio of MACl to CsI is 0.93-0.97:0.03-0.07.

Citation Information

Cited By

  • Controllable steam atmosphere assisted perovskite thin film crystallization method

    CN120344120A

  • A controllable steam atmosphere-assisted perovskite thin film crystallization method

    CN120344120B